Aeroplane View, Fort Dearborn (Max Rigot Selling Co)
Blockhouse and soldiers' barracks of the "third Fort Dearborn", reappear on the shore of Lake Michigan as part of the 1934 Century of Progress Exposition. Near here stood the original blockhouse and barracks of the old fort whose inhabitants were victims in 1812 of the Dearborn Massacre eventful day in Chicago's Pioneer history.